Escape rooms: A new offer in the recreation sector in Poland - Stasiak, Andrzej (Turyzm/Tourism, 2016)
Globalization leaves its footprint on the leisure market contributing to the global popularization of brand new forms of recreation. A perfect example of such instant diffusion of innovation on a global scale is the rapid development of escape rooms. The aim of the article is to try and explain the extraordinary popularity of escape rooms in Poland, mainly through an analysis of what they offer. The author presents the origins and development of this particular form of recreation, discusses the location of nearly 600 facilities functioning in 2016, as well as giving a detailed description of escape rooms in the ten large Polish cities. The study leads to the conclusion that the phenomenon of escape rooms stems from, among other things, the fundamental assumptions of the experience economy.